Analyze the Loss of Electricity in Palestine Case Study: Ramallah and Al-Bireh Governorate - Jawad, Yousef Abdel; Ayyash, Issam (International Journal of Energy Economics and Policy, 2019)
The study aimed to investigate the factors leading to the loss of electricity in Ramallah and Al-Bireh Governorate in Palestine. In order to achieve the objectives of the study, descriptive and quantitative analysis was used in this study. Based on the data of the Jerusalem Electricity Company, and the data of the Palestinian Central Bureau of Statistics for 2010-2018, the Ordinary Least Squares method (OLS) was used in regression analysis, and by Granger Causality Test the hypotheses were tested using Eviews. The study found that there is a causal negative relationship between wages, the number of pre-paid electricity meters, fines imposed on violators, and the number of participants on the loss of electricity. While there was no causal relationship between the price of electricity, the unemployment rate, the rate of education, and spending on maintenance on the loss of electricity. Keywords: Electricity losses, Electricity theft, Non- Technical loss. JEL Classifications: B41, C13, C22, Q49. DOI: https://doi.org/10.32479/ijeep.8325